Eco-environmental assessment of industrial wastewater treatment for sustainability and potable reuse - Gour, Reetu; Gori, Yatika; Kumar, Ashwani; Awasthi, Mukesh Kumar (Edelweiss Applied Science and Technology, 2025)
Currently, water pollution remains a major global concern, and sustainable wastewater treatment is essential to addressing water scarcity and achieving potable water standards. This article presents an integrated environmental and sustainability assessment of an advanced industrial wastewater treatment system for a textile industry generating 2,000 m³/day of effluent. A hybrid treatment system, comprising a membrane bioreactor (MBR), activated carbon filtration, and reverse osmosis (RO), achieved significant pollutant removal: 98.6% COD, 99.3% TSS, and 95.1% heavy metals (Pb, Cd, Cr). The treated water met WHO drinking water standards with TDS <300 mg/L, and microbial contaminants are undetectable. Sustainability metrics showed an 87% water recovery rate and a specific energy consumption of 2.8 kWh/m³. Life Cycle Assessment (LCA) revealed a 32% lower carbon footprint than conventional methods, while economic analysis estimated a treatment cost of $0.92/m³ and a 6.5-year payback period when combined with water reuse. Additionally, this research focused on the potential of microalgae-based bioremediation as an eco-friendly alternative. Microalgae offer effective nutrient recovery, greenhouse gas reduction, and biomass valorization for biofuels, fertilizers, food additives, and therapeutic compounds. Thus, microalgae integration presents a cost-effective, sustainable solution for wastewater treatment and bioenergy production.